2016
DOI: 10.4103/2231-0746.200326
|View full text |Cite
|
Sign up to set email alerts
|

The use of buccal fat pad free graft in closure of soft-tissue defects and dehiscence in the hard palate

Abstract: Introduction:The integrity of the palatal mucosa can be lost due to congenital, pathological, and iatrogenic conditions. Various surgical techniques have been suggested for the closure of palatal defects. The aim of the current study is to present the free buccal fat pad graft as a novel technique to repair the soft-tissue defects at the palate.Patients and Methods:During a 2-year period, the free fat tissue graft harvested from the buccal fat pad (BFP) (FBFG) and used to reconstruct five soft-tissue defects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Protocols to prevent these potential complications could include the displacement of the buccal fat pad [ 53 , 54 ] over the zygomatic implant body, or the ZAGA Scar Graft [ 55 ]. In the present case series, the buccal fat pad was chosen given the harvesting simplicity of the approach with minor complications, easy manipulation, easy handling of the graft, anatomical proximity, and proven results [ 53 , 54 , 56 ]. Nevertheless, controlled studies are lacking that compare the two alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Protocols to prevent these potential complications could include the displacement of the buccal fat pad [ 53 , 54 ] over the zygomatic implant body, or the ZAGA Scar Graft [ 55 ]. In the present case series, the buccal fat pad was chosen given the harvesting simplicity of the approach with minor complications, easy manipulation, easy handling of the graft, anatomical proximity, and proven results [ 53 , 54 , 56 ]. Nevertheless, controlled studies are lacking that compare the two alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…The trismus after the surgery is very low 17 . It can be used easily in the closure of OACs that occur in the first and second upper premolar in comparison with the PBFP.…”
Section: Discussionmentioning
confidence: 99%
“…[3334] Following several years of handling the fat tissue by the author in various clinical applications in the maxillofacial field, it is now well established that fat tissue from the BFFG can survive and heal very well, so it can be used as an excellent tissue graft in different defects in the oral cavity. [24252627] In a previous study, it was demonstrated by the author that the BFFG heals by fast epithelialization of its exposed parts on the one hand and simultaneous fibrosis of the graft that proceeds from immature fibrosis to full maturation after 4 months on the other hand. [24]…”
Section: Discussionmentioning
confidence: 99%
“…The BFFG successfully covered different hard palate defects. [27] De Castro et al , in 2015, in their case report, described the use of FFG for closure of oronasal fistula and suggested it as a treatment option for some cases of anterior maxillary defects. [28] The current study reports additional clinical application of the BFFG and suggests the use of this graft as a predictable new method for treatment of severe GR at different sites in both maxillary and mandibular teeth.…”
Section: Introductionmentioning
confidence: 99%